Materiality of Writing in Early Mesopotamia - Balke, Thomas E. (Materiale Textkulturen, 2016)
This volume presents recent research on the relationship between the material format of text-bearing artefacts, the texts they carry, and their genre. The essays cover a vast period, from the counting stones of the late 4th millennium BCE to the time of the Great Hittite Kingdom in the 2nd millennium BCE. The breadth of substantive focus allows new insights of relevance to scholars in both Ancient Middle Eastern studies and the humanities.